Recurrent CLTC::SYK fusions and CSF1R mutations in juvenile xanthogranuloma of soft tissue - Kemps, Paul; Baelde, Hans J.; Vorderman, Ruben H. P.; Stelloo, Ellen; Swennenhuis, Joost F.; Szuhai, Karoly; Lamers, Meindert H.; Kenkhuis, Boyd; Al-Hussaini, Maysa; Briaire-de Bruijn, Inge H.; Lam, Suk Wai; Bovée, Judith V. M. G.; et al. (Blood, 2024)
Juvenile xanthogranuloma (JXG) is a histiocytic neoplasm that usually presents in the skin. Rarely, extracutaneous localizations occur; the genetic drivers of this clinical variant of JXG remain incompletely characterized. We present detailed clinicopathologic and molecular data of 16 children with extracutaneous JXG and 5 adults with xanthogranulomas confined to the central nervous system (CNS) or soft tissue. Tissue samples were obtained through the Dutch Nationwide Pathology Databank and analyzed with an innovative sequencing technique capable of detecting both small genomic variants and gene rearrangements. Targetable kinase alterations were detected in 16 of 16 children and 1 of 5 adults. Alterations included CLTC::SYK fusions in 6 children and CSF1R mutations in 7 others; all below 2 years of age with soft tissue tumors. One child had a CSF1R mutation and MRC1::PDGFRB fusion. Most were treated surgically, although spontaneous regression occurred in 1 of 6 with CLTC::SYK and 2 of 7 with CSF1R mutations, underscoring that treatment is not always necessary. Tumors with CLTC::SYK fusions generally lacked Touton giant cells but exhibited many other histologic features of JXG and concordant methylation profiles. Using multispectral immunofluorescence, phosphorylated-spleen tyrosine kinase expression was localized to CD163+ histiocytes; tumors with CLTC::SYK fusions also demonstrated mTOR activation, cyclin D1 expression, and variable phosphorylated-extracellular signal-regulated kinase expression. BRAFV600E was detected in 1 child and 1 adult with CNS-xanthogranulomas; both responded to BRAF inhibition. Finally, a TPM3::NTRK1 fusion or MAP2K1 deletion was detected in 2 children with systemic JXG who experienced spontaneous disease regression. This study advances the molecular understanding of histiocytic neoplasms and may guide diagnostics and clinical management.